2020
DOI: 10.3390/ijerph17249580
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Young Schoolchildren’s Intake of Sugar-Rich Food and Drinks: Study Protocol and Intervention Design for “Are You Too Sweet?” A Multicomponent 3.5-Month Cluster Randomised Family-Based Intervention Study

Abstract: A high consumption of sugar-rich discretionary food and drinks has several health implications, which have been traced from childhood into adulthood. Parents act as primary mediators shaping children’s dietary habits, and interventions that engage parents have shown to result in positive outcomes. Further, collaboration with local school health nurses and dentists provides an effective structural frame to support behaviour change and anchor new initiatives. The multicomponent 3.5-month cluster randomised famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
(73 reference statements)
1
21
0
Order By: Relevance
“…16,17 In this study the uses of the fruits, biscuits, lemonade and coca cola, sugar, tea and chew gum was found to be frequent while use of the honey was very lower. Similar findings were made by Mishra A. et al 18 in their research, which showed that youngsters consumed more sugar on a daily basis from cakes, creams, sweets, and candies than from fruits. Two factors may be used to explain this rise in the consumption of carbohydrates: first, they are readily available to the general public in the form of processed food, and children are drawn to them by their appealing look and marketing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…16,17 In this study the uses of the fruits, biscuits, lemonade and coca cola, sugar, tea and chew gum was found to be frequent while use of the honey was very lower. Similar findings were made by Mishra A. et al 18 in their research, which showed that youngsters consumed more sugar on a daily basis from cakes, creams, sweets, and candies than from fruits. Two factors may be used to explain this rise in the consumption of carbohydrates: first, they are readily available to the general public in the form of processed food, and children are drawn to them by their appealing look and marketing.…”
Section: Discussionsupporting
confidence: 89%
“…Children fill up on sweets and other sugary foods when they aren't eating during their free time. 18,20 In this study betel nut use was high but it was not found habitual. However, According to a cross-sectional survey conducted in Taiwan, 50% of primary school children in indigenous areas have chewing tobacco, including 30.1% who chew habitually 21 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…At the beginning of the intervention study 160 families signed up. The details of the study have been described in the study protocol [ 15 ]. In total, 95 children, i.e., the intervention group of project “Are you to sweet” were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Another area of concern is that dietary behaviors in childhood may persist into adulthood (18). As such, intervention studies have been devoted to investigate how to promote healthy food choices and dietary habits and limit FS intake effectively among children (19)(20)(21). In Saudi Arabia and the Middle East, data regarding intake of FS are lacking.…”
Section: Introductionmentioning
confidence: 99%